Urgent request on avian influenza. (30th January 2017) - ; More, S; Bicout, D; Bøtner, A; Butterworth, A; Calistri, A; Depner, K; Edwards, S; Garin-Bastuji, B; Good, M; Gortázar Schmidt, C; Michel, V; et al.
Abstract: HPAI H5N8 is currently causing an epizootic in Europe, infecting many poultry holdings as well as captive and wild bird species in more than ten countries. Given the clear clinical manifestation, passive surveillance is considered the most effective means of detecting infected wild and domestic birds. Testing samples from new species and non‐previously reported areas is key to determine the geographic spread of HPAIV H5N8 2016 in wild birds. Testing limited numbers of dead wild birds in previously‐reported areas is useful when it is relevant to know whether the virus is still present in the area or not, e.g. before restrictive measures in poultry are to be lifted. To prevent introduction of HPAIV from wild birds into poultry, strict biosecurity implemented and maintained by the poultry farmers is the most important measure. Providing holding‐specific biosecurity guidance is strongly recommended as it is expected to have a high impact on the achieved biosecurity level of the holding. This is preferably done during peace time to increase preparedness for future outbreaks. The location and size of control and in particular monitoring areas for poultry associated with positive wild bird findings are best based on knowledge of the wider habitat and flight distance of the affected wild bird species. It is recommended to increase awareness among poultry farmers in these established areas in order to enhance passive surveillance and to implement enhanced biosecurity measures including poultry confinement. There is no scientific evidence suggesting a different effectiveness of the protection measures on the introduction into poultry holdings and subsequent spread of HPAIV when applied to H5N8, H5N1 or other notifiable HPAI viruses. Abstract : This publication is linked to the following EFSA Supporting Publications article:http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2016.EN-1142/full